Massive Interfacial Reconstruction at Misfit Dislocations in Metal/Oxide Interfaces - Choudhury, Samrat (Nature Publishing Group, 2014)
Electronic structure calculations were performed to study the role of misfit dislocations on the structure and chemistry of a metal/oxide interface. We found that a chemical imbalance exists at the misfit dislocation which leads to dramatic changes in the point defect content at the interface – stabilizing the structure requires removing as much as 50% of the metal atoms and insertion of a large number of oxygen interstitials. The exact defect composition that stabilizes the interface is sensitive to the external oxygen partial pressure. We relate the preferred defect structure at the interface to a competition between chemical and strain energies as defects are introduced.